Polycarbonate modified alloy composition, modified alloy material and preparation method and application thereof

By mixing components such as bio-based isodol-type polycarbonate and bisphenol-A polycarbonate with antistatic agents, carbon black and carbon nanotubes in a specific proportion, and preparing them through melt extrusion process, the problems of insufficient antistatic properties, gloss and blackness of PC/ASA alloy materials are solved, and the appearance of high gloss black and excellent antistatic properties are achieved.

CN119842201APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311347819.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing polycarbonate/styrene-acrylonitrile-acrylic rubber copolymer (PC/ASA) alloy materials have insufficient antistatic properties, gloss and blackness, resulting in the accumulation of static electricity, whitening surface of the material and light color.

Method used

Polycarbonate modified alloy materials are prepared by mixing bio-based isodol-type polycarbonate, bisphenol-A polycarbonate, styrene-acrylonitrile-acrylic rubber copolymer with antioxidants, mold release agents, compatibility agents, toughening agents, antistatic agents, carbon black and carbon nanotubes in a specific proportion, and the polycarbonate modified alloy material is prepared by melt extrusion process.

Benefits of technology

The prepared polycarbonate modified alloy material has excellent antistatic properties, high gloss and blackness, and maintains good impact resistance, heat resistance and flowability, meeting the requirements of high-gloss black appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of polycarbonate modified alloy compositions, and discloses a polycarbonate modified alloy composition, a modified alloy material as well as a preparation method and application of the polycarbonate modified alloy composition and the modified alloy material. The polycarbonate modified alloy composition is prepared from the following components in parts by weight: 20 to 50 parts of first polycarbonate, 10 to 50 parts of second polycarbonate, 10 to 50 parts of styrene-acrylonitrile-acrylic rubber copolymer, 0.1 to 0.5 part of antioxidant, 0.1 to 0.5 part of release agent, 1 to 3 parts of compatilizer, 1 to 8 parts of flexibilizer and 2 to 10 parts of antistatic agent, 2-15 parts by weight of carbon black; and 0.5-5 parts by weight of carbon nanotubes. The modified alloy material prepared from the polycarbonate modified alloy composition provided by the invention has excellent antistatic property, meets the appearance requirements of higher blackness and glossiness, and is good in heat resistance, impact resistance and flowability; the preparation method disclosed by the invention is simple in process, high in production efficiency and capable of realizing large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polycarbonate modified alloy compositions, and in particular to a polycarbonate modified alloy composition, a modified alloy material, and a preparation method and application thereof. Background Art

[0002] Polycarbonate / styrene-acrylonitrile-acrylic rubber copolymer (PC / ASA) belongs to the polycarbonate alloy category. It has the excellent properties of PC and ASA, and has excellent impact resistance, heat resistance, high strength and other characteristics. It is widely used in the manufacture of various automotive interior parts. However, since PC and ASA resins are good electrical insulation materials with high volume resistivity and surface resistivity, static electricity is easily accumulated during use, causing electronic components to age and electronic equipment to malfunction. It can also cause dust, dirt and other particles to be adsorbed, which is difficult to clean. In severe cases, electric sparks may be generated, leading to fires.

[0003] With the development of the automobile industry, car interiors with black as the main color are favored by many consumers. However, light scatters on the plastic surface, causing the material surface to turn white, and absorption causes the color to fade. Crystalline materials have crystalline regions and amorphous regions with different refractive indices, and the scattering phenomenon is obvious; transparent substrates have little light scattering and high transmittance, which is suitable for the production of high-gloss black raw materials. Ordinary polycarbonate (usually bisphenol A aromatic polycarbonate) has a benzene ring rigid group on the molecular chain, and the steric hindrance effect is large, while bio-based polycarbonate has chirality and a rigid bicyclic monomer structure, and has a higher transmittance than bisphenol A polycarbonate, which is more suitable for the production of high-gloss black raw materials.

[0004] Isosorbide raw material, as a bio-based monomer from renewable resources, is a good choice to replace bisphenol A polycarbonate. However, isosorbide is highly hydrophilic and the steric hindrance effect of its molecular structure leads to low hydroxyl activity. The rigid ring structure in its molecular structure also makes the prepared polycarbonate have poor impact resistance and poor toughness.

[0005] Therefore, it is urgent to develop a polycarbonate modified alloy material with antistatic properties and high gloss black appearance to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of poor antistatic performance, low gloss and blackness of PC / ASA alloy materials in the prior art, and to provide a polycarbonate modified alloy composition, a modified alloy material, and a preparation method and application thereof. The polycarbonate modified alloy material prepared from the polycarbonate modified alloy composition provided by the present invention has good antistatic performance, high gloss and blackness, as well as good impact resistance, fluidity and heat resistance.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a polycarbonate modified alloy composition, wherein the composition comprises the following components: 20-50 parts by weight of a first polycarbonate, 10-50 parts by weight of a second polycarbonate, 10-50 parts by weight of a styrene-acrylonitrile-acrylic rubber copolymer, 0.1-0.5 parts by weight of an antioxidant, 0.1-0.5 parts by weight of a release agent, 1-3 parts by weight of a compatibilizer, 1-8 parts by weight of a toughening agent, 2-10 parts by weight of an antistatic agent, 2-15 parts by weight of carbon black and 0.5-5 parts by weight of carbon nanotubes.

[0008] The second aspect of the present invention provides a polycarbonate modified alloy material, which is obtained by melt extrusion of the above-mentioned composition.

[0009] The third aspect of the present invention provides a method for preparing a polycarbonate modified alloy material, the method comprising:

[0010] (1) mixing a first polycarbonate, a second polycarbonate, a styrene-acrylonitrile-acrylic rubber copolymer, an antioxidant, a release agent, a compatibilizer, a toughening agent, an antistatic agent, carbon black and carbon nanotubes to obtain a premix;

[0011] (2) Melt-extrude the premix under negative pressure to obtain the polycarbonate modified alloy material.

[0012] A fourth aspect of the present invention provides an application of the composition described in the first aspect or the polycarbonate modified alloy material described in the second aspect in charging piles, outdoor electronic appliances, electric meter housings and vehicle exterior trims.

[0013] Through the above technical solution, the present invention has the following beneficial effects:

[0014] (1) The polycarbonate modified alloy composition provided by the present invention is mainly composed of bio-based isoidene polycarbonate, bisphenol A polycarbonate and styrene-acrylonitrile-acrylic rubber copolymer, and is supplemented with appropriate amounts of toughening agent, compatibilizer, antioxidant, demoulding agent, antistatic agent, carbon black and carbon nanotubes. The surface resistivity of the prepared polycarbonate modified alloy material is less than 1×10 10 Ω·cm, static decay time is less than 1s, L value is lower than 27, glossiness is higher than 102, it has excellent antistatic properties and meets the appearance requirements of higher blackness and glossiness.

[0015] (2) The polycarbonate modified alloy material provided by the present invention adopts a scheme of compounding bio-based isoidine polycarbonate and bisphenol A polycarbonate. On the basis of retaining the original PC / ASA performance, the heat resistance and impact resistance of the modified alloy material are improved, and the fluidity of the modified alloy material is greatly enhanced. Relying on the compatibilizer, it can ensure that the bio-based isoidine polycarbonate is well compatible with bisphenol A polycarbonate and styrene-acrylonitrile-acrylic rubber copolymer, thereby fundamentally reducing the internal stress and stress cracking of the modified alloy material.

[0016] (3) The polycarbonate modified alloy material provided by the present invention effectively disperses multi-walled carbon nanotubes in polycarbonate, thereby improving the antistatic effect of the modified alloy material. In addition, the addition of conductive carbon black and antistatic agent has a certain synergistic effect on the antistatic performance of the modified alloy material, thereby reducing the surface resistance of the modified alloy material, making the antistatic effect of the modified alloy material better, and reducing the amount of expensive antistatic agent. In addition, the preparation method has a simple process and high production efficiency, conforms to the concept of green environmental protection, can realize industrial production, and meet the demand of the high-end application market for polycarbonate modified alloy materials. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The first aspect of the present invention provides a polycarbonate modified alloy composition, wherein the composition comprises the following components: 20-50 parts by weight of a first polycarbonate, 10-50 parts by weight of a second polycarbonate, 10-50 parts by weight of a styrene-acrylonitrile-acrylic rubber copolymer, 0.1-0.5 parts by weight of an antioxidant, 0.1-0.5 parts by weight of a release agent, 1-3 parts by weight of a compatibilizer, 1-8 parts by weight of a toughening agent, 2-10 parts by weight of an antistatic agent, 2-15 parts by weight of carbon black, and 0.5-5 parts by weight of carbon nanotubes.

[0019] In the present invention, the polycarbonate modified alloy composition includes bio-based isoindole type polycarbonate, bisphenol A type polycarbonate, styrene-acrylonitrile-acrylic rubber copolymer, antioxidant, release agent, compatibilizer, toughening agent, antistatic agent, carbon black and carbon nanotubes. The amount of the composition is controlled within the range defined in the present invention. By compounding the components, it can be ensured that the further prepared modified alloy material has excellent antistatic performance, impact resistance, heat resistance and fluidity, does not crack during long-term use, and can meet the appearance requirements of high black light.

[0020] In some embodiments of the present invention, preferably, the first polycarbonate is a bio-based isoidoacetate-type polycarbonate; and the weight average molecular weight of the first polycarbonate is 21000-25000 g / mol.

[0021] In some embodiments of the present invention, preferably, the first polycarbonate has a melt index of 2-8 g / 10 min at 300° C. and a load of 1.2 kg.

[0022] In the present invention, the first polycarbonate can be self-made. Preferably, under the action of a titanium catalyst, iso-iditol and molten diphenyl carbonate in a mass ratio of 1:1.0-1.1 are prepared by an ester exchange method to obtain the first polycarbonate, wherein the amount of the titanium catalyst is 0.1-0.15 mol%. In the present invention, the biological toxicity of the iso-iditol is very small, and the use of the bio-based iso-iditol polycarbonate defined in the present invention as a raw material can reduce the toxicity of the product and expand the application field of the product; and the bio-based iso-iditol polycarbonate has a chiral and rigid bicyclic monomer structure, has a higher light transmittance, and is more conducive to the production of high-gloss black polycarbonate modified alloy materials.

[0023] In some embodiments of the present invention, preferably, the second polycarbonate is selected from aromatic polycarbonates, more preferably bisphenol A polycarbonate.

[0024] In some embodiments of the present invention, preferably, the weight average molecular weight of the second polycarbonate is 20000-40000 g / mol; the melt index of the second polycarbonate at 300°C and a load of 1.2 kg is 5-25 g / 10 min. In the present invention, the second polycarbonate can be obtained commercially, for example, the second polycarbonate can be purchased from Dafeng Chemical Industry with a brand number of 02-20.

[0025] In the present invention, the above-defined bio-based isoindrol-type polycarbonate is compounded with bisphenol A-type polycarbonate, which is beneficial to improve the heat resistance and impact resistance of the modified alloy material while retaining the original PC / ASA performance, and can meet the appearance requirements of the high-gloss black modified alloy material.

[0026] In some embodiments of the present invention, preferably, in the styrene-acrylonitrile-acrylic rubber copolymer, the weight percentage of acrylic rubber is 50-70%.

[0027] In some embodiments of the present invention, preferably, the melt index of the styrene-acrylonitrile-acrylic rubber copolymer at 220° C. and a load of 10 kg is 5-15 g / 10 min. In the present invention, the styrene-acrylonitrile-acrylic rubber copolymer can be obtained commercially, for example, the styrene-acrylonitrile-acrylic rubber copolymer can be purchased from Chi Mei Company, Taiwan, China, with a brand name of PW-978B.

[0028] In some embodiments of the present invention, preferably, the antioxidant is selected from hindered phenol antioxidants and / or phosphite antioxidants, more preferably selected from one or two of [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris[2,4-di-tert-butylphenyl]phosphite. In the present invention, the antioxidant is used to ensure stable performance of the material processing process, ensure color stability during the processing stage, and provide long-term use guarantee.

[0029] In some embodiments of the present invention, preferably, the release agent is selected from at least one of stearic acid amide lubricants, hydrocarbon lubricants and fatty acid lubricants, and more preferably pentaerythritol tetrastearate. In the present invention, the release agent can ensure smooth demoulding of the material.

[0030] In some embodiments of the present invention, preferably, the compatibilizer is an epoxy functional group grafted polymer, more preferably a glycidyl methacrylate grafted styrene-acrylonitrile copolymer, wherein the epoxy resin content is 0.5-10wt%. In the present invention, the epoxy resin content range defined by the compatibilizer can ensure good compatibility between the polycarbonate phase and the styrene-acrylonitrile-acrylic rubber copolymer phase, improve the interface strength, fundamentally reduce the internal stress and stress cracking of the modified alloy material, and improve the mechanical properties of the modified alloy material.

[0031] In the present invention, the compatibilizer contains glycidyl methacrylate, and an increase in the amount of glycidyl methacrylate promotes the bonding force between the carbon nanotubes and the compatibilizer. Excessive glycidyl methacrylate reduces the dispersibility of the carbon nanotubes in the modified alloy material, thereby reducing the conductivity of the material; in addition, excessive compatibilizer increases the haze of the surface of the modified alloy material, thereby reducing the glossiness of the surface of the modified alloy material.

[0032] In some embodiments of the present invention, preferably, the toughening agent is an acrylic core-shell impact modifier. In the present invention, the toughening agent has a core-shell structure, can be particularly well dispersed in the modified alloy material, can be mixed in a twin-screw or single-screw extruder, and because its core is an organosilicon polymer, can improve the toughness of the modified alloy material, and can improve the compatibility of the polycarbonate phase and the styrene-acrylonitrile-acrylic rubber copolymer phase in the modified alloy material. In addition, the toughening agent can be obtained commercially, for example, the toughening agent can be purchased from M577 of Japan's Kanebuchi.

[0033] In some embodiments of the present invention, preferably, the antistatic agent is a reagent containing a polyetheresteramide block copolymer. In the present invention, the antistatic agent can reduce the surface resistivity of the plastic polymer, achieve an electrostatic dustproof effect, and enable the modified alloy material to achieve a long-term antistatic effect.

[0034] In some embodiments of the present invention, preferably, the carbon black is conductive carbon black with an oil absorption of 34-44 mL / 100 g. In the present invention, the carbon black has the characteristics of high filling and easy dispersion, so that the modified alloy material has excellent extrudability, low gas permeability and low compression deformation.

[0035] In some embodiments of the present invention, preferably, the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5-15 nm, a length of 1-3 μm, a purity of more than 90%, and a volume resistivity of 10 -3 -10 -5 Ω·cm, density is 1.6-1.9g / cm 3 In the present invention, the multi-walled carbon nanotubes have high structural properties, which endow the polycarbonate with higher tensile strength and impact strength as well as excellent electrical conductivity. The multi-walled carbon nanotubes are used in combination with carbon black and an antistatic agent to reduce the surface resistance of the modified alloy material, thereby making the modified alloy material have a better antistatic effect and reducing the amount of the expensive antistatic agent.

[0036] The second aspect of the present invention provides a polycarbonate modified alloy material, which is obtained by melt extrusion of the above-mentioned composition.

[0037] In some embodiments of the present invention, preferably, the notched impact strength of the modified alloy material is greater than 40 kJ / m 2 , preferably 40.35-48.48 kJ / m 2 ; Surface resistivity <1×10 10 Ω·cm, preferably 7.24×10 8 -7.24×10 9Ω·cm; static decay time <1s, preferably 0.18-0.59s; gloss >102, preferably 102.2-103.8; L value <27, preferably 25.7-26.9.

[0038] In the present invention, bio-based isoindrol-type polycarbonate is introduced for alloying to improve the high gloss black appearance requirement of the modified alloy material. With the addition of additives, the prepared modified alloy material has good impact resistance and heat resistance, and the antistatic performance of the modified alloy material is greatly improved.

[0039] A third aspect of the present invention provides a method for preparing a polycarbonate modified alloy material, the method comprising:

[0040] (1) mixing a first polycarbonate, a second polycarbonate, a styrene-acrylonitrile-acrylic rubber copolymer, an antioxidant, a release agent, a compatibilizer, a toughening agent, an antistatic agent, carbon black and carbon nanotubes to obtain a premix;

[0041] (2) The premix is ​​melt-extruded to obtain the polycarbonate modified alloy material.

[0042] In the present invention, the composition described in step (1) is added to a high-speed mixer according to the corresponding weight and fully mixed for 3-5 minutes to obtain a premix; the premix is ​​fed from the main feeding port of a twin-screw extruder, melted, plasticized, sheared, and dispersed under negative pressure conditions, and then extruded through a die head, pulled, cooled, granulated, and homogenized to obtain the polycarbonate modified alloy material.

[0043] In some embodiments of the present invention, preferably, the melt extrusion is carried out in a twin-screw extruder, wherein the screw aspect ratio of the twin-screw extruder is 32-40:1, the screw temperature is 170-270°C; the negative pressure is -0.075MPa to -0.08MPa. In the present invention, the screw aspect ratio, screw temperature and pressure are controlled within the range defined by the present invention, which is conducive to better melt extrusion process. The prepared polycarbonate modified alloy material meets the appearance requirements of high gloss black antistatic, and has excellent antistatic performance, impact resistance, heat resistance and fluidity. It does not crack after long-term use. The preparation method is simple, the production efficiency is high, and it conforms to the concept of green environmental protection.

[0044] In some embodiments of the present invention, preferably, the temperatures of the screws in each section of the twin-screw extruder include: the temperature of the feeding zone in zone 1 is 170-190°C, the temperature of the pressure zone in zone 2 is 230-260°C, the temperature of the pressure zone in zone 3 is 230-260°C, the melting temperature in zone 4 is 230-260°C, the exhaust temperature in zone 5 is 220-250°C, the conveying temperature in zone 6 is 230-270°C, the pressure temperature in zone 7 is 220-250°C, the temperature of the devolatilization zone in zone 8 is 230-260°C, the pressure zone in zone 9 is 220-250°C, and the head temperature is 230-260°C. In the present invention, the temperature of each screw section is controlled within the range specified in the present invention, so that the prepared polycarbonate modified alloy material has the technical effect of the present invention; in addition, if the temperature of each screw section is higher than the range specified in the present invention, the material will be further decomposed during the extrusion process, thereby reducing the physical properties; if the temperature of each screw section is lower than the range specified in the present invention, the melt fluidity of the material during the extrusion process is too poor, which is not conducive to extrusion processing.

[0045] A fourth aspect of the present invention provides an application of the composition described in the first aspect or the polycarbonate modified alloy material described in the second aspect in charging piles, outdoor electronic appliances, electric meter housings and vehicle exterior trims.

[0046] The present invention will be described in detail below through examples.

[0047] The performance testing described includes the following tests:

[0048] Melt index test: Tested in accordance with ISO1133 "Determination of mass flow rate and volume flow rate of thermoplastic melts" standard, the test conditions are 260℃ / 5kg·10min;

[0049] Notched impact strength test: The test was conducted in accordance with ISO 179 "Determination of impact strength of simply supported beams of plastics". The length of the polycarbonate modified alloy material sample tested was 80 mm, the width was 10 mm, and the thickness was 4 mm.

[0050] Heat deformation temperature test: The test was conducted in accordance with ISO 75-1 "Determination of load deformation temperature of plastics". The length of the polycarbonate modified alloy material sample tested was 80 mm, the width was 10 mm, and the thickness was 4 mm.

[0051] Surface resistivity and electrostatic decay time test: According to IEC61340-5-1 2008 "Electronic equipment is protected from electrostatic phenomena - General requirements" and ANSI / ESDS20.20-2007 "Establishing an electrostatic discharge control program for the protection of electrical and electronic parts, devices and equipment (excluding electric detonators)" standards, the tested polycarbonate modified alloy material sample has a width of 80mm, a length of 120mm, a thickness of 1mm, a surface resistivity test voltage of 100V, and a charging time of 20s;

[0052] Gloss test: According to GB / T8807-1988 "Test method for specular gloss of plastics", the length of the polycarbonate modified alloy material sample tested is 150mm, the width is 100mm, and the test condition is 60° incident angle;

[0053] Test color plate color: measured by a colorimeter, L value calculated according to the relevant provisions of GB / T3979-2008 "Measurement method of object color", the length of the tested polycarbonate modified alloy material sample is 100mm, and the width is 50mm.

[0054] The raw materials used in the following examples and comparative examples are:

[0055] Bio-based isoidol-based polycarbonate is prepared by using an ester exchange method with isoidol and molten diphenyl carbonate in the presence of a titanium catalyst, with a weight average molecular weight of 21,000-25,000 g / mol and a melt index of 2-8 g / 10 min at 300° C. and a load of 1.2 kg.

[0056] Bisphenol A polycarbonate was purchased from Dafeng Chemical Industry, with a grade of 02-20, a weight average molecular weight of 26000 g / mol, and a melt index of 20 g / 10 min at 300°C and a load of 1.2 kg;

[0057] Styrene-acrylonitrile-acrylic rubber copolymer was purchased from Chi Mei Company, Taiwan, China, with a brand name of PW-978B, and a melt index of 5 g / 10 min at 220°C and a load of 10 kg;

[0058] The antioxidants are hindered phenol antioxidants and / or phosphite antioxidants purchased from BASF;

[0059] The release agent was purchased from Minke New Materials Co., Ltd. Pentaerythritol tetrastearate;

[0060] The compatibilizer was purchased from Jiangsu Jiayirong, brand SAG-002;

[0061] The toughening agent was purchased from Japan's Kanebuchi, brand M577;

[0062] The antistatic agent was purchased from Sanyo Chemical, brand name PELESTAT 6500;

[0063] Carbon black was purchased from Orilon Engineering Carbon Company, brand CORAX N990, oil absorption was 34-44 mL / 100 g;

[0064] Carbon nanotubes were purchased from Belgium Nanocyl, with a brand name of NC7000, a diameter of 5-15 nm, a length of 1-3 μm, a purity of >90%, and a volume resistivity of 10 -3 -10 -5 Ω·cm, density is 1.6-1.9g / cm 3 .

[0065] Examples 1-6

[0066] According to the materials in Table 1, the polycarbonate modified alloy material was prepared. The steps are as follows:

[0067] (1) adding bio-based isoidoacetate, bisphenol A polycarbonate, styrene-acrylonitrile-acrylic rubber copolymer, antioxidant, release agent, compatibilizer, toughening agent, antistatic agent, carbon black and carbon nanotubes according to the weight parts in Table 1 into a high-speed mixer, and mixing them thoroughly for 3-5 minutes to obtain a premix;

[0068] (2) feeding the premix from the main feeding port of the twin-screw extruder, controlling the pressure to be -0.075 to -0.08 MPa, melting, plasticizing, shearing, and dispersing the premix in the extruder, extruding through a die head, pulling, cooling, granulating, and homogenizing to obtain a polycarbonate modified alloy material;

[0069] Among them, the screw length-diameter ratio is controlled to be 40:1, and the extrusion segmented temperature zones are as follows: the temperature of the feeding zone in zone 1 is 170-190℃, the temperature of the pressure zone in zone 2 is 230-260℃, the temperature of the pressure zone in zone 3 is 230-260℃, the melting temperature in zone 4 is 230-260℃, the exhaust temperature in zone 5 is 220-250℃, the conveying temperature in zone 6 is 230-270℃, the pressure building temperature in zone 7 is 220-250℃, the temperature of the devolatilization zone in zone 8 is 230-260℃, the temperature of the pressure building zone in zone 9 is 220-250℃, and the temperature of the die head is 230-260℃.

[0070] Comparative Examples 1-6

[0071] The method for preparing the polycarbonate modified alloy material is the same as that of Examples 1-6, according to the materials in Table 1 (Continued).

[0072] Table 1 Components and weight parts of each embodiment and comparative example

[0073]

[0074]

[0075] Table 1 (continued)

[0076]

[0077] The modified alloy materials obtained in Examples 1 to 6 and Comparative Examples 1 to 6 were subjected to performance tests, and the test results are shown in Table 2:

[0078] Table 2 Test results

[0079]

[0080] Table 2 (continued)

[0081]

[0082] It can be seen from the results in Table 2 that the method of the present invention can be used to obtain a high gloss black antistatic bio-based PC / ASA modified alloy material. It can be seen from Examples 1-6 that the bio-based iso-ido alcohol type polycarbonate, bisphenol A type polycarbonate, ASA, antioxidant, release agent, compatibilizer, toughening agent, antistatic agent, carbon black and carbon nanotubes are controlled within the range defined by the present invention, and the notched impact strength of the obtained modified alloy material is higher than 40 kJ / m 2 , with good impact resistance; the fluidity is greater than 38g / 10min, with excellent processing resistance; the heat deformation temperature is greater than 98℃, with good heat resistance; the surface resistivity is less than 1×10 10 Ω·cm, the static decay time is less than 1s, and it has good antistatic properties; and the glossiness of the modified alloy materials is higher than 102, and the L value is lower than 27, with high glossiness and blackness. Comparative Example 1 does not use the bio-based isoidene alcohol type polycarbonate defined in the present invention, and the residual bisphenol A content of the modified alloy material obtained is higher than 20ppm, and the antistatic property and blackness are relatively poor; Comparative Examples 2-4 do not use the content of antistatic agent, carbon black, and carbon nanotubes defined in the present invention, respectively, and the surface resistivity of the modified alloy material obtained is high, and the antistatic property is poor; Comparative Example 5 does not use the content of toughening agent defined in the present invention, and the notched impact strength of the modified alloy material obtained is greatly reduced, and the impact strength is poor; Comparative Example 6 does not use the content of compatibilizer defined in the present invention, and the antistatic property of the modified alloy material obtained is relatively poor, and the excessively high content of compatibilizer reduces the glossiness of the modified alloy material.

[0083] The effect of the present invention can be achieved only when the amount of each of the above components is controlled within the range defined by the present invention. The modified alloy material prepared by the method described in the present invention has good antistatic properties, meets the appearance requirements of high blackness and glossiness, and also has excellent impact resistance, heat resistance and fluidity, and has a simple preparation process, high production efficiency, and is convenient for industrial production.

[0084] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polycarbonate modified alloy composition, characterized in that: The composition comprises the following components: 20-50 parts by weight of a first polycarbonate, 10-50 parts by weight of a second polycarbonate, 10-50 parts by weight of a styrene-acrylonitrile-acrylic rubber copolymer, 0.1-0.5 parts by weight of an antioxidant, 0.1-0.5 parts by weight of a release agent, 1-3 parts by weight of a compatibilizer, 1-8 parts by weight of a toughening agent, 2-10 parts by weight of an antistatic agent, 2-15 parts by weight of carbon black and 0.5-5 parts by weight of carbon nanotubes.

2. The composition according to claim 1, characterized in that The first polycarbonate is a bio-based isoidide polycarbonate; Preferably, the weight average molecular weight of the first polycarbonate is 21000-25000 g / mol; Preferably, the first polycarbonate has a melt index of 2-8 g / 10 min at 300° C. and a load of 1.2 kg.

3. The composition according to claim 1 or 2, characterized in that The second polycarbonate is selected from aromatic polycarbonate, preferably bisphenol A polycarbonate; Preferably, the weight average molecular weight of the second polycarbonate is 20000-40000 g / mol; Preferably, the second polycarbonate has a melt index of 5-25 g / 10 min at 300° C. and a load of 1.2 kg.

4. The composition according to any one of claims 1 to 3, characterized in that In the styrene-acrylonitrile-acrylic rubber copolymer, the weight percentage of acrylic rubber is 50-70%; Preferably, the styrene-acrylonitrile-acrylic rubber copolymer has a melt index of 5-15 g / 10 min at 220° C. and a load of 10 kg.

5. The composition according to any one of claims 1 to 4, characterized in that The antioxidant is selected from hindered phenol antioxidants and / or phosphite antioxidants, preferably selected from one or two of [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris[2,4-di-tert-butylphenyl]phosphite; Preferably, the release agent is selected from at least one of stearic acid amide lubricants, hydrocarbon lubricants and fatty acid lubricants, preferably pentaerythritol tetrastearate; Preferably, the compatibilizer is an epoxy functional group grafted polymer, preferably a glycidyl methacrylate grafted styrene-acrylonitrile copolymer, wherein the epoxy resin content is 0.5-10wt%; Preferably, the toughening agent is an acrylic core-shell impact modifier; Preferably, the antistatic agent is an agent containing a polyetheresteramide block copolymer; Preferably, the carbon black is conductive carbon black, and the oil absorption is 34-44 mL / 100 g; Preferably, the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5-15 nm, a length of 1-3 μm, a purity of more than 90%, and a volume resistivity of 10 -3 -10 -5 Ω·cm, density is 1.6-1.9g / cm 3 .

6. A polycarbonate modified alloy material, characterized in that: Obtained by melt extrusion of the composition according to any one of claims 1 to 5; Preferably, the notched impact strength of the modified alloy material is greater than 40 kJ / m 2 , preferably 40.35-48.48 kJ / m 2 ; Surface resistivity <1×10 10 Ω·cm, preferably 7.24×10 8 -7.24×10 9 Ω·cm; static decay time <1s, preferably 0.18-0.59s; gloss >102, preferably 102.2-103.8; L value <27, preferably 25.7-26.

9.

7. A method for preparing a polycarbonate modified alloy material, characterized in that: The method includes: (1) mixing a first polycarbonate, a second polycarbonate, a styrene-acrylonitrile-acrylic rubber copolymer, an antioxidant, a release agent, a compatibilizer, a toughening agent, an antistatic agent, carbon black and carbon nanotubes to obtain a premix; (2) Melt-extrude the premix under negative pressure to obtain the polycarbonate modified alloy material.

8. The method according to claim 7, characterized in that The melt extrusion is carried out in a twin-screw extruder, wherein the screw aspect ratio of the twin-screw extruder is 32-40:1, the screw temperature is 170-270°C; and the negative pressure is -0.075MPa to -0.08MPa.

9. The method according to claim 8, characterized in that The screw temperatures of each section in the twin-screw extruder include: the temperature of the feeding zone in zone 1 is 170-190°C, the temperature of the pressure building zone in zone 2 is 230-260°C, the temperature of the pressure building zone in zone 3 is 230-260°C, the melting temperature in zone 4 is 230-260°C, the exhaust temperature in zone 5 is 220-250°C, the conveying temperature in zone 6 is 230-270°C, the pressure building temperature in zone 7 is 220-250°C, the temperature of the devolatilization zone in zone 8 is 230-260°C, the temperature of the pressure building zone in zone 9 is 220-250°C, and the head temperature is 230-260°C.

10. Use of the composition according to any one of claims 1 to 5 or the polycarbonate modified alloy material according to claim 6 in charging piles, outdoor electronic appliances, electric meter housings and vehicle exterior trims.